PENGARUH PELATIHAN MARKETING ONLINE TERHADAP LITERASI DIGITAL UMKM BERBASIS MASJID - Wahyu Bagja Sulfemi (Ikatan Sarjana Al-Qur'an Indonesia (ISQI), 2026)
The rapid development of digital technology has encouraged Micro, Small, and Medium Enterprises (MSMEs) to utilize digital platforms as effective tools for business development and marketing activities. However, limited digital literacy remains a significant challenge for many MSME actors in optimizing the use of digital technology. This study aims to examine the effect of online marketing training on the digital literacy of mosque-based MSMEs participating in the BMM Al Amin program. The research employed a mixed-method approach with a sequential explanatory design, integrating quantitative and qualitative data to provide a comprehensive understanding of the phenomenon. The participants consisted of 29 MSME actors who attended the online marketing training program. Data were collected through questionnaires, interviews, observations, and documentation. Quantitative data were analyzed using the Pearson Product-Moment correlation, coefficient of determination, and t-test, while qualitative data were analyzed through data reduction, data display, and conclusion drawing. The findings revealed that online marketing training had a positive and significant effect on the digital literacy of mosque-based MSMEs. The correlation coefficient of 0.611 indicated a strong relationship between online marketing training and digital literacy. The coefficient of determination showed that online marketing training contributed 37.31% to the improvement of participants’ digital literacy, while the remaining 62.69% was influenced by other factors beyond the scope of this study. The hypothesis testing results demonstrated that the calculated t-value (4.008) was higher than the t-table value (2.052) at a 5% significance level, confirming the acceptance of the research hypothesis. Qualitative findings further indicated that the training enhanced participants’ ability to utilize social media, create promotional content, use WhatsApp Business, expand customer networks, and increase business motivation. This study concludes that online marketing training serves as an effective strategy for improving the digital literacy of mosque-based MSMEs and strengthening the role of mosques in community economic empowerment in the digital era.